Student Adoption and Effectiveness of Flipped Classroom Implementation for Process Simulation Class - Muhammad Syafiq Hazwan Ruslan; Nurul Haiza Sapiee; Kiki Adi Kurnia; Nurul Aini Amran; Norazah Abd Rahman (Education Sciences, 2022)
A flipped classroom (FC) teaching approach offers a personalized learning environment for the learners to study the course using pre-recorded material prior to the in-class session. The synchronous sessions are then dedicated to knowledge confirmation and learning activities. Although this technique is considered promising, the learners’ acceptance of FC for skill-based courses conducted entirely via open distance learning (ODL) has yet to be assessed in Malaysia. Thus, this study aims to evaluate the FC approach's effectiveness and student readiness and acceptance during ODL. A questionnaire was used to assess the students’ adoption and overall implementation of FC. Results show that students who underwent the FC approach gave a better performance in their course. In fact, 39.29% of the students who underwent the FC approach managed to score A and A- compared to 19.82% of students that went for conventional delivery. Regarding the adoption, 100% of the surveyed students agreed that the pre-recorded video assisted them in preparing for the class. Furthermore, 100% of students surveyed agreed that they were able to prepare the simulation before the next class at the end of the semester, compared to 96.154% in the first 4 weeks. It can be concluded that the FC approach has been shown to be effective and easily adopted by students. Furthermore, the FC learning framework has been developed to map the learning activities and the learning domain. Principles such as How People Learn and Bloom taxonomy were embedded in the development of this framework.